INDONESIAN TO ENGLISH SINGABLE TRANSLATIONS BY LOCAL AND FOREIGN TRANSLATORS - Andika Wijaya; Gloria Christine Setiyowati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
Song lyric translation is important because in these recent decades people can access songs worldwide. The aim of this research is to gain an understanding of the difference between singable translations made by an Indonesian translator and a foreign translator by investigating what translation procedures and methods occur in two translated songs from Indonesian to English using qualitative descriptive method. The result of this research indicates that the singable translation made by a foreign translator is more identical to the source language (SL) compared to the one made by an Indonesian translator. However, despite the differences, the two translated songs share something in common, for instance the singability and the length of lyrics. Taking the findings into consideration, it could be said that the foreign translator is more faithful to the source text (ST), while the Indonesian translator emphasizes the target language (TL) more.